Mosque and Environmental Issues: A Research Path Analysis - As-Salafiyah, Aisyah; Uula, Mimma Maripatul; Taufiq, Muhammad (SMART Insight, 2024)
Mosques play an important role in the social structure of Muslim communities. Mosque functions are not only limited to religious functions, but also play an important role in addressing various social problems faced by the community as well as environmental issues, such as raising awareness and knowledge related to environmental cleanliness, energy resources, and waste management, where these roles are integrated with Islamic principles. The purpose of this study is to see the development of research on the topic of